Proximate and Organoleptic Levels of Tempeh Made from Cowpeas from Southwest Maluku and Its Integration in Community Learning - Karmila, Wa Ode; Karuwal, Ritha Lusian; Rehena, Johanis F (Program Studi Pendidikan Biologi, Pascasarjana, Universitas Pattimura, 2024)
Cowpea (Vigna unguiculata) is a type of bean that is well known and developed in Indonesia. One area in Indonesia that has the potential for these nuts is Southwest Maluku. Utilization in local communities is still limited. Therefore, the development of food products such as tempeh is considered. In making tempeh, the dosage of yeast determines the success of fermentation. To be suitable for consumption, nutritional and organoleptic composition testing is required. Thus, this research aims to analyze the proximate and organileptic levels of tempeh made from cowpeas from Southwest Maluku. The study used a Completely Randomized Design treatment with a yeast dose of 0.1 g; 0.2g; 0.4 g repeated 3 times. The data obtained were analyzed using the Anova test (one way) and continued with the DMRT test on SPSS software version 26.0. The research results showed that yeast dosage had a significant effect on ash, fat and fiber content and had high organoleptic value. Treatment two (P2) has a high nutritional composition and the best organoleptic value compared to other treatments. Thus, tempeh made from cowpeas from Southwest Maluku with a yeast dose of 0.2 g can be recommended for development as a food product for the people of Southwest Maluku.